The Ambivalence of Hawthorne in Twice Told Tales - Marandi, Seyyed Mohammad; Ramin, Zohreh (Richtmann Publishing, 2011)
As inheritors of the Puritan religious tradition, the notion of 'consciousness` is a major concept in the works of mostAmerican writers. Hawthorne's employment of this conception in his works is observable in his employment of a highly art-consciousvoice who intrudes, every now and then, to pose questions, and provide various possibilities of alternate endings and solutions, but neverattempting to come up with an ultimate point of resolution. Ambivalence arises as the result of this authorial intrusion and as the presentpaper attempts to reveal, is the result of an author highly conscious of the art of writing. Hawthorne's employment of this specific techniqueof authorial intrusion itself becomes a paradoxical attempt at simultaneously revealing and concealing the art of fiction-writing. Instancesof such ambivalence are drawn from his collection of Twice Told Tales.However, the present reading of the tales attempts to reveal that Hawthorne is not totally successful in his intension to secure his superiorrole as author, as the very breaches he provides within his stories open the possibility for further meaning and interpretation, thusdepriving him of the very power he desires to preserve.